Formation flying along libration point orbits using chattering attenuation sliding mode control - Bando, Mai; Namati, Hamidreza; Akiyama, Yuki; Hokamoto, Shinji (Frontiers in Space Technologies, 2022)
This paper studies a control law to achieve formation flying in cislunar space. Utilizing the eigenstructure of the linearized flow around a libration point of the Earth-Moon circular restricted three-body problem, the fuel efficient formation flying controller based on the chattering attenuation sliding mode controller is designed and analyzed. Numerical studies are conducted for the Earth-Moon L2 point and a halo orbit around it. The total velocity change required to achieve formation as well as to maintain the orbit is calculated. Simulation results show that the chattering attenuation sliding mode controller has good performance and robustness in the presence of unmodeled nonlinearity along the halo orbit with moderate fuel consumption.